Palestinian social media and lone-wolf attacks: subculture, legitimization, and epidemic - Chorev-Halewa, Harel (Terrorism and political violence, 2019)
This article examines the impact of social media on the wave of Palestinian lone-wolf attacks against Israelis from October 2015 through September 2016. My principal argument is that social media played an important role in shaping the identity, perceptions, and behavioral patterns of dozens of assailants, and was key in creating the dynamic that ultimately characterized both the spreading of the idea of lone-wolf attacks and its execution. Social media reflected reality on the ground while simultaneously nourishing, amplifying, and escalating the situation by providing a platform for the emergence of new sources of authority, including an online subculture with distinct codes and pseudo-ritual patterns to support assailants. Social media also contributed substantially to shaping the contagious character of the attacks, and their capacity to persist without direct organizational guidance, following a typical epidemiological dynamic of spread, containment, and preservation.